Digital humanism : a philosophy for 21st century digital society - Fuchs, Christian, 1976- (Emerald Publishing Limited, 2022)
Our contemporary global digital society is not always a good place to live. Authoritarianism, hatred, false news, post-truth culture, the COVID-19 anti-vaccination movement, COVID-19 conspiracy theories, and political polarisation are organised via the Internet. The public sphere is highly polarised. Today, many humans tend to think of other humans mainly in terms of friends and enemies. Robots and Artificial Intelligence-based automation have created new challenges for the world of work. Decades of neoliberalism have increased inequalities. The COVID-19 pandemic has shown the vulnerability of humanity to viruses and health crises. Humanity and society are in a major crisis and digitalisation mediates this crisis. Digital Humanism explores how Humanism can help us to critically understand how digital technologies shape society and humanity, providing an introduction to Humanism in the digital age. Fuchs introduces the approach of Digital Humanism and outlines foundations of a Radical Digital Humanism, analysing what decolonisation of academia and the study of the digital, media and communication means; what the roles are of robots, automation, and Artificial Intelligence in digital capitalism, and how the communication of death and dying has been mediated by digital technologies, capitalist necropower, and digital capitalism. In order to save humanity and society, we need Radical Digital Humanism now.
Keywords: Digital media -- Social aspects.; Technology -- Social aspects.; Humanism.; Social Science, Technology Studies.; Ethical issues: scientific & technological developments.; elektronické knihy; electronic books